The closed circle : joining and leaving the Muslim Brotherhood in the West - Vidino, Lorenzo (Columbia studies in terrorism and irregular warfare., 2020)
"While often the subject of heated debates, the Muslim Brotherhood in the West remains a mysterious entity. Scholars, security officials, journalists and policymakers disagree on virtually every aspect of the issue, starting with the most basic questions: what the Brotherhood in the West is, who belongs to it, how one joins it, how it operates, how it finances itself--and, in some cases, on whether it even exists. In this book, Lorenzo Vidino uses the stories of individuals who joined and later left Western outfits of the Muslim Brotherhood in order to understanding the inner workings of this group and the tactics it uses to recruit and retain members. The Muslim Brotherhood may be only one of many extremist organizations trying to gain a foothold in the West, but Vidino's unprecedented access and understanding of the group's everyday activities and motivations gives him an opportunity to explore the underlying mechanisms found in all sorts of terrorist organizations"--